6.3: Glasses‐free Virtual Reality for Rehabilitation of Stroke Survivors. (28th November 2018) - Zhang, Hantao; Lin, Luqi; Liu, Yuan; Yu, Jiatong; Wang, Jiahui; Liang, Haowen; Zhou, Jianying; Chen, Ling; Li, Le; Mao, Yurong; Huang, Dongfeng
Abstract : Different from conventional head‐mounted virtual reality, we achieve a high quality glasses‐free virtual reality (VR) platform by combining full HD directional backlight 3D display with gesture controller. The glasses‐free VR display enables full resolution, low crosstalk and wide viewing angle, which is able to provide precise depth information. Attributed to the excellent 3D effect without any assisting goggles, our glasses‐free VR can be used for rehabilitation of stroke patients. Compared with the traditional 2D training, it offers the third dimension for the patients to imagine and practice their upper‐limb joints, showing better performance for stroke rehabilitation.